Pemberdayaan Keluarga Penerima Manfaat (Kpm) Program Keluarga Harapan (Pkh) Melalui Literasi Keuangan Dan Pengembangan Usaha Mikro Di Desa Medanglayang - Risdawanty Risdawanty; Sani Haryati (CV. SINAR HOWUHOWU, 2026)
Program Keluarga Harapan (PKH) is a conditional cash transfer program designed to improve the welfare of poor families in Indonesia. However, many beneficiary families (KPM) have not been able to manage the assistance productively, particularly in the areas of financial management and productive business development. This community service activity aimed to improve financial literacy and promote economic independence of KPM PKH in Desa Medanglayang through counseling, training, and mentoring approaches. The results showed a meaningful increase in participants' understanding of household financial management, the ability to record simple finances, and the emergence of micro-business initiatives. Overall, the activity had a positive impact on the economic independence of KPM PKH in the village.